Improvement of Artificial Limb Cup to Investigate Loads by Using Load Sensors - Hussien, Mohammed Barzan; MohammedSaeed, Noorhan Ibrahim (Central Asian Journal of Medical and Natural Science, 2025)
The construction, adaptation and lifelong treatment of amputee's artificial limbs are particularly difficult tasks in the field of rehabilitation medicine. Traditional approaches rely on static clinical measurements and subjective patient feedback, which results in the collection of severely inadequate data for dynamic loads and socket interface pressures during daily use. This lack of periodic monitoring often leads to poor socket fit, gait asymmetry, skin breakdown and patient discomfort - conditions that can sometimes go unheeded until there is a need for clinical intervention. It is common for prosthetic device delivery to end post-manufacture and without patients' providers having integrated systems that provide feedback on the prosthesis performance once it has been issued. To address this engineering gap, the present study presents the design, development, and initial testing of a novel sensor-based monitoring system for prosthetic sockets. The novelty is in the intentional incorporation of a network hydrostatic high-definition thin-film load cell / pressure sensor, under either the liner or wall of pylon.None! This system is developed to investigate and measure pressures and shearing forces between limb-socket during “everyday” activities: walking, climbing stairs, standing. The information collected by such sensors is processed using an onboard microcontroller and wirelessly sent to a clinician interface for analysis. The primary goal of this work is to transition prosthetic modeling away from being observation-oriented and static, into a dynamic data-based process. Serving as a data basis for load distribution, and gait symmetric, this apparatus makes it possible to diagnose fitting errors and running abnormalities lucidly. Such knowledge enables prompt adjustments of socket design and alignment that may prove instrumental in preventing secondary health concerns. In addition, this data can inform personalized physical rehabilitation protocols. Adoption of this monitoring option is a major advancement in the field of prosthetics, with expected positive impact including increased patient comfort, improved functionality and reduced long-term healthcare costs based on outcomes-driven clinical decision making.